ANALYSIS OF WIRELESS NETWORK SIMULATION BASED ON OPENWRT AND PFSENSE WITH QUALITY OF SERVICE INDICATORS ON LOW-COST NETWORK INFRASTRUCTURE - Mishbahuddin, Ahmad; Hatta, Puspanda; Budiyanto, Cucuk Wawan (Informatika, Universitas Jenderal Soedirman, 2024)
The need for high network traffic in Indonesia with the challenge of geographical topology that is difficult to reach makes the majority of internet network users access via wireless networks with limited budgets, resulting in poor internet QoS in Indonesia. An available solution to optimize low-cost network quality is to use the OpenWRT, open source router operating system with a focus on ease of application implementation in network projects. Another solution is pfSense, which is an open source router operation with a firewall network security focus to prevent intrusion. These two operating systems have different comparison methods in performance testing, making it difficult to make decisions about the performance differences between the two operating systems. This study aims to analyze the difference in performance and significance of open source operating systems with different development focuses on low-cost wireless network services. Analysis obtained from the quality of service measurement method on OpenWRT and Pfsense router operating systems on users that connected to a simulated wireless network topology. Data was collected by sending data between a number of users to the server and vice versa using iperf3 and mtr tools. The data consisted of QoS parameters: troughput, delay, jitter, and packet loss. The data shows that there are significant differences in several QoS parameters in the service of a number of users between the OpenWRT and PfSense operating systems. The results of this study show the limitations of each operating system in its implementation in low-cost wireless networks.